Penanaman Perilaku Hidup Bersih dan Sehat di SDN Plumbungan “Healthy Lifestyle for Healthy Life” - Ratnasari, Sri Dwi; Muslimah Eka Apriliani; Endah Dwi Rawanti; Dwi Dita Dyah P; Darra Nandang Trisno; Alifa Hanun N (Journal of Social Empowerment, 2024)
This activity is one of the work program implementations of the Kampus Mengajar at SDN Plumbungan which aims to provide knowledge and practice of PHBS for students at SDN Plumbungan. The main targets are students from grade 1 to grade 6. The implementation of the activity was carried out on November 9 and 24 November 2023. The methods used are planning, implementation, and evaluation. The results of community service entitled Planting Clean and Healthy Living Behavior at SDN Plumbungan with the theme "Healthy Lifestyle for Healthy Life" went well. Students are very enthusiastic in understanding the materials presented about PHBS, practicing hand washing properly and correctly, and practicing Jemuah Sehat with the theme "contents of my plate" which is nutritionally balanced. This activity reinforces students' awareness in maintaining health and hygiene, especially in the school environment.